2014
DOI: 10.1007/s10802-014-9908-3
|View full text |Cite
|
Sign up to set email alerts
|

Irritable and Defiant Sub-Dimensions of ODD: Their Stability and Prediction of Internalizing Symptoms and Conduct Problems from Adolescence to Young Adulthood

Abstract: Emerging research has identified sub-dimensions of oppositional defiant disorder - irritability and defiance - that differentially predict internalizing and externalizing symptoms in preschoolers, children, and adolescents. Using a theoretical approach and confirmatory factor analyses to distinguish between irritability and defiance, we investigate the associations among these dimensions and internalizing (anxiety and depression) and externalizing problems (conduct problems) within and across time in a communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 33 publications
6
61
0
1
Order By: Relevance
“…From age 3 to age 9, both internalizing and externalizing symptoms showed moderate and between construct associations. Consistent with the literature (Dougherty et al, 2013, 2015; Leadbeater & Homel, 2015), age 3 persistent irritability was moderately positively correlated with both concurrent and later internalizing and externalizing symptoms. Both the ΔERN and the ERN were correlated with age and total number of errors, such that a greater differentiation between error and correct trials and a larger negativity to errors was associated with older age and fewer errors.…”
Section: Resultssupporting
confidence: 87%
“…From age 3 to age 9, both internalizing and externalizing symptoms showed moderate and between construct associations. Consistent with the literature (Dougherty et al, 2013, 2015; Leadbeater & Homel, 2015), age 3 persistent irritability was moderately positively correlated with both concurrent and later internalizing and externalizing symptoms. Both the ΔERN and the ERN were correlated with age and total number of errors, such that a greater differentiation between error and correct trials and a larger negativity to errors was associated with older age and fewer errors.…”
Section: Resultssupporting
confidence: 87%
“…Consistent with hypotheses, the headstrong/hurtful dimension at age 11 was uniquely predictive of substance use disorder symptoms (specifically alcohol and cannabis), antisocial behavior, and overall externalizing problems 6 years later at age 17. Taken together with the findings of others (Aebi et al., ; Leadbeater & Homel, ; Rowe et al., ), these results suggest that the headstrong/hurtful dimension has lasting predictive power and may provide an early sign for the development of externalizing psychopathology in late adolescence and early adulthood.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Leadbeater and Homel (44) reported that ODD symptoms among adolescents were linked with both internalizing (anxiety and depression) and externalizing (conduct problems) problems. Boylan et al (45) also indicated that ODD is often comorbid with internalizing disorders (anxiety/depressive disorder) in childhood and adolescence.…”
Section: Discussionmentioning
confidence: 99%